2004
DOI: 10.2190/8x6d-hfh5-w27r-09f9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Knowledge and Beliefs of Finnish Medical Students regarding HIV Infection and Participation in AIDS Vaccine Trials

Abstract: This study sought to determine the level of general knowledge about HIV infection among Finnish medical students and their willingness to participate in AIDS vaccine trials. One hundred and sixty-two volunteer medical students at the University of Kuopio in the 2nd and 5th years of training filled self-administered questionnaires. The overall response rate among the 2nd year students was 77%, and among the 5th year students 70%. Knowledge was scored on a percentage scale. The mean score on general knowledge ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Students’ HH knowledge scores improved over the duration of the course, which is supported by previous studies demonstrating that knowledge on a topic may increase over time. For example, Onigbogi et al. (2005–2006) found that the mean score on a questionnaire in relation to Human Immunodeficiency Virus was higher in fifth year medical students than in second year medical students.…”
Section: Discussionmentioning
confidence: 99%
“…Students’ HH knowledge scores improved over the duration of the course, which is supported by previous studies demonstrating that knowledge on a topic may increase over time. For example, Onigbogi et al. (2005–2006) found that the mean score on a questionnaire in relation to Human Immunodeficiency Virus was higher in fifth year medical students than in second year medical students.…”
Section: Discussionmentioning
confidence: 99%